One hundred years after Pinctada: an update on alien Mollusca in Tunisia - ANTIT, M.; GOFAS, S.; SALAS, C.; AZZOUNA, A. (Mediterranean Marine Science, 2011)
The occurrences of non-indigenous marine molluscs in Tunisia are reviewed, based booth on a literature survey and on original material. Species are accepted as established if there are two independent reports, either geographically separate or at least one month apart in time. On these grounds, 14 species are accepted (12 alien and 2 expanding their range from elsewhere in the Mediterranean), 3 aliens need confirmation but are likely to meet the standards for acceptation on a short future, and 5 records are rebutted or questioned. Two more species may be considered as cryptogenic, the reports are reliable but it is not clear indication that they are not indigenous. Two of the alien species are reported for the first time in Tunisian waters: the nudibranch Polycerella emertoni qualifies as established, and the bivalve Anadara transversa is tentatively identified from a juvenile live-taken specimen, which awaits further confirmation. The occurrence of aliens in Tunisia is balanced between presumably Lessepsian species of tropical Indo-Pacific origin, and species from other sources including species from the Tropical Atlantic introduced through shipping. Nevertheless there is a prevalence of Lessepsian species towards the Gulf of Gabes in the south, whereas the shipping activity in Tunis harbour may be the main pathway of introduction in the north.